Synthesis and identification of deschloroketamine metabolites in rats' urine and a quantification method for deschloroketamine and metabolites in rats' serum and brain tissue using liquid chromatography tandem mass spectrometry - Hájková, Kateřina; Jurásek, Bronislav; Čejka, Jan; Štefková, Kristýna; Páleníček, Tomáš; Sýkora, David; Kuchař, Martin (Drug testing and analysis, 2020)
Deschloroketamine (2-(methylamino)-2-phenyl-cyclohexanone) is a ketamine analog belonging to a group of dissociative anesthetics, which have been distributed within the illicit market since 2015. However, it was also being sold as 'ketamine' misleading people to believe that they were getting genuine ketamine. Dissociative anesthetics have also come to the attention of the psychiatric field due to their potential properties in the treatment of depression. At present, there is a dearth of information on deschloroketamine related to its metabolism, biodistribution, and its mechanism of action. We have therefore carried out a metabolomics study for deschloroketamine via non-targeted screening of urine samples employing liquid chromatography combined with high-resolution mass spectrometry. We developed and validated a multiple reaction monitoring method using a triple quadrupole instrument to track metabolites of deschloroketamine. Furthermore, significant metabolites of deschloroketamine, (trans-dihydrodeschloroketamine, cis- and trans-dihydronordeschloroketamine, and nordeschloroketamine), were synthesized in-house. The prepared standards were utilized in the developed multiple reaction monitoring method. The quantification method for serum samples provided intra-day accuracy ranging from 86% to 112% with precision of 3% on average. The concentrations of cis/trans-dihydronordeschloroketamines and trans-dihydrodeschloroketamine were lower than 10 ng/mL, nordeschloroketamine and deschloroketamine ranged from 0.5 to 860 ng/mL in real samples. The quantification method for brain tissue provided intra-day accuracy ranging from 80% to 125% with precision of 7% on average. The concentrations of cis/trans-dihydronordeschloroketamines and trans-dihydrodeschloroketamine ranged from 0.5 to 70 ng/g, nordeschloroketamine and deschloroketamine varied from 0.5 to 4700 ng/g in real samples.
Keywords: krysa rodu Rattus; Animals; Ketamine; tkáňová distribuce; zvířata; mužské pohlaví; Male; tandemová hmotnostní spektrometrie; Chromatography, Liquid; Brain; Tissue Distribution; Rats; chromatografie kapalinová; mozek; ketamin; Tandem Mass Spectrometry